Decadal reanalysis of biogeochemical indicators and fluxes in the North West European shelf‐sea ecosystem. Issue 3 (20th March 2016) - Ciavatta, S.; Kay, S.; Saux‐Picart, S.; Butenschön, M.; Allen, J. I.
Abstract: This paper presents the first decadal reanalysis simulation of the biogeochemistry of the North West European shelf, along with a full evaluation of its skill, confidence, and value. An error‐characterized satellite product for chlorophyll was assimilated into a physical‐biogeochemical model of the North East Atlantic, applying a localized Ensemble Kalman filter. The results showed that the reanalysis improved the model simulation of assimilated chlorophyll in 60% of the study region. Model validation metrics showed that the reanalysis had skill in matching a large data set of in situ observations for 10 ecosystem variables. Spearman rank correlations were significant and higher than 0.7 for physical‐chemical variables (temperature, salinity, and oxygen), ∼0.6 for chlorophyll and nutrients (phosphate, nitrate, and silicate), and significant, though lower in value, for partial pressure of dissolved carbon dioxide ( ∼ 0.4). The reanalysis captured the magnitude of pH and ammonia observations, but not their variability. The value of the reanalysis for assessing environmental status and variability has been exemplified in two case studies. The first shows that between 325, 000 and 365, 000 km 2 of shelf bottom waters were vulnerable to oxygen deficiency potentially threatening bottom fishes and benthos. The second application confirmed that the shelf is a net sink of atmospheric carbon dioxide, but the total amount of uptake varies between 36 and 46 Tg C yr −1 at a 90% confidence level. These results indicate that the reanalysis output data set can inform the management of the North West European shelf ecosystem, in relation to eutrophication, fishery, and variability of the carbon cycle. Key Points: The reanalysis data set is skilled in estimating indicators that are relevant for marine policy There is high confidence of oxygen deficiency in large areas of shelf bottom waters The shelf‐sea ecosystem is a net sink of atmospheric carbon dioxide (CO2 )